Digital Drugs And Their Negative Impact On Youth And Society (Journal of Namibian Studies : History Politics Culture, 2024)
Modern societies have witnessed astounding advancements in technology. Among these societies, some have succeeded in harnessing this technology, while others face a real danger that threatens their members, especially with the recent phenomenon of addiction to digital drugs. This phenomenon has spread tremendously across various social strata, manifesting psychological, social, and deviant effects, particularly among the youth—a demographic that remains vulnerable in the face of these significant technological developments. Due to the absence of legal, human, or material deterrents, this phenomenon has worsened. Today, youth are exposed to the circulation and addiction to digital drugs, leading to numerous behavioral deviations. From this arises the main question of this discourse: How do digital drugs affect our youth?